Clinical Implications of Heart Rate Control in Heart Failure With Atrial Fibrillation: Multi-Center Prospective Observation Registry (CODE-AF Registry) - Song, Shinjeong; Ko, Jum-Suk; Lee, Hye Ah; Choi, Eue-Keun; Cha, Myung-Jin; Kim, Tae-Hoon; Park, Jin-Kyu; Lee, Jung-Myung; Kang, Ki-Woon; Shim, Jaemin; Uhm, Jae-Sun; Kim, Jun; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Atrial fibrillation (AF) is treated by heart rate (HR) control. However, the optimal HR target in AF patients with heart failure (HF) remains unclear. To evaluate the clinical implication of the resting HR in AF patients with HF accompanied by preserved, mid-range, or reduced ejection fraction (HFpEF, HFmrEF, or HFrEF, respectively). Methods Echocardiographic data from June 2016 to April 2020 in a prospective, multicenter, observational registry from 11,104 patients were analyzed. The follow-up duration was 2.2 years. The main outcome was composite of death and hospitalization. We categorized patients according to the HF type and resting HR: ≤60 bpm, 61–80 bpm, 81–110 bpm, and >110 bpm. Results A total of 1,421 patients were enrolled in the study: 582 in the HFpEF group, 506 in the HFmrEF group, and 333 in the HFrEF group. The patients had a mean age of 69 ± 11 years and consisted of 872 (61.4%) men. Primary endpoint rates among HFpEF patients with 60110 bpm strata). In HFmrEF and HFrEF patients, the survival rates did not differ significantly among patients in the three groups with HR ≤110 bpm. Moreover, the event rates increased significantly in HFmrEF patients with HR >110 bpm (hazard ratio, 1.91; 95% CI, 1.16-3.14, p = 0.011) Conclusion In patients with AF and HFpEF, the resting HR has U-shaped associations with the overall primary endpoint. A lower or higher resting HR is associated with increased cardiovascular outcomes, especially in patients with HFpEF and AF.